Measurement of the correlation between flow harmonics of different order in lead-lead collisions at √sNN = 2.76 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
Correlations between the elliptic or triangular flow coefficients υm(m = 2 or 3) and other flow harmonics υn(n = 2 to 5) are measured using√sNN = 2.76 TeV Pb + Pb collision data collected in 2010 by the ATLAS experiment at the LHC, corresponding to an integrated luminosity of 7 μb−1. The υm-υncorrelations aremeasured in midrapidity as a function of centrality, and, for events within the same centrality interval, as a function of event ellipticity or triangularity defined in a forward rapidity region. For events within the same centrality interval, υ3is found to be anticorrelated with υ2and this anticorrelation is consistent with similar anticorrelations between the corresponding eccentricities, ϵ2and ϵ3. However, it is observed that υ4increases strongly with υ2, and υ5increases strongly with both υ2and υ3. The trend and strength of the υm-υncorrelations for n = 4 and 5 are found to disagree with ϵm-ϵncorrelations predicted by initial-geometry models. Instead, these correlations are found to be consistent with the combined effects of a linear contribution to υnand a nonlinear term that is a function of υ2 2or of υ2υ3, as predicted by hydrodynamic models. A simple two-component fit is used to separate these two contributions. The extracted linear and nonlinear contributions to υ4and υ5are found to be consistent with previously measured event-plane correlations.